Ground Vehicle Dynamics - Popp, Karl.; Schiehlen, Werner; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Ground Vehicle Dynamics is devoted to the mathematical modelling and dynamical analysis of ground vehicle systems composed of the vehicle body, the guidance and suspension devices and the corresponding guideway. Automobiles on uneven roads and railways on flexible tracks are prominent representatives of ground vehicle systems. All these different kinds of systems are treated in a common way by means of analytical dynamics and control theory. In addition to a detailed modelling of vehicles as multibody systems, the contact theory for rolling wheels and the modelling of guideways by finite element systems as well as stochastic processes are presented. As a particular result of this integrated approach the state equations of the global systems are obtained including the complete interactions between the subsystems considered as independent modules. The fundamentals of vehicle dynamics for longitudinal, lateral and vertical motions and vibrations of automobiles and railways are discussed in detail.
System Definition and Modeling -- Vehicle Models -- Models for Support and Guidance Systems -- Guideway Models -- Models for Vehicle-Guideway-Systems -- Assessment Criteria -- Computational Methods -- Longitudinal Motions -- Lateral Motions -- Vertical Motions.
Keywords: Engineering; Vibration; Control engineering systems; Engineering; Vibration, Dynamical Systems, Control; Automotive Engineering; Control , Robotics, Mechatronics